Tina Hana Ventures Sales Management System (THV-SMS) / Shamshul Nur Fatinah Shamshul Arifin - Shamshul Arifin, Shamshul Nur Fatinah (2017)
Recording sales and ordering is one of the most crucial processes in a business. Tina Hana Ventures (THV) is currently using manual ways to produce reports and only save ordering information in the chatting application group, Whatsapp. This problem causes the business to not be able to produce proper report for their financial and failed to do systematic filing. Tina Hana Ventures Sales Management System (THV- SMS) is a system that is developed to assist THV to track and record their daily order and sales in order to produce accurate data for their company reports and financial and also to handle their trade secret securely. There are three types of users in the system which are staff, manager and administrator and the system is accessible through the web as the system applying web-based application. Enterprise Resource Planning (ERP) is chosen as the theory of the project as it is the most suitable and beneficial to apply in the system. The elements implemented in THV-SMS are customer order management, human resource management and finance. The methodology used to develop THV-SMS is prototyping model. Prototyping model is chosen due to the request on participation from the owner of THV and also in order to confirm with THV on the elements needed in the system for the business. THV- SMS was evaluated by users by using questionnaire and the owner of THV during the prototype development. The questionnaire is distributed to the 30 respondents and evaluated based on six constructs which are ease of use, ease of learning, usefulness, satisfaction, efficiency and consistency. The result shows that respondents agreed on the usefulness construct with highest mean which is 3.99 which means they agree with that the system is useful and agrees in other aspects evaluated.